Bantuek kan sevana "por khon Thai luem ngai fan rai jueng ma yuen" pad me kor ha song - Sawasdipol, Khattiya.
'Because Thai people are easy in forgetting, that's why the nightmare comes : seminar record 8 March 2009'. Includes speeches of Seh Daeng. Red Shirt movement collection.